Implementation of Students' Creativity Through Differentiated Learning Methods Using The Independent Curriculum in Elementary Schools - Riskiyah, Mazidatur; Indah Sari, Aprilia Sri; Aisyah, Novita Nur; Almarzuki, Ainul Yakin; Hardiansyah, Framz (Journal of Practice Learning and Educational Development, 2026)
Curriculum changes that adapt to the needs of students, societal demands, and current developments. One of them is the development of the independent learning curriculum. This study aims to examine the implementation of the independent curriculum on the development of student creativity. With a differentiated learning method, namely adapting to the unique learning of each student by considering their characteristics, skills, interests, and learning preferences. This study uses library research through a qualitative approach. Data collection techniques in this study use documentation techniques in the form of notes, transcripts, books, newspapers, magazines, inscriptions, minutes, research results, and so on. The collected data are then analyzed using descriptive methods. The results of the study indicate that the form of implementation of the independent curriculum in elementary schools is the use of technology, preparing learning tools, implementing learning strategies that are appropriate to interests and talents, learning is adapted to the situation and environmental conditions, as well as local wisdom, socio-economics and providing space for students to learn collaboratively. Therefore, it can be understood that the implementation of the independent curriculum has an impact on increasing student creativity to produce innovation in education.